1981
DOI: 10.1073/pnas.78.2.829
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functional domains of the heparin molecule.

Abstract: Affinity-fractionated porcine heparin was randomly scissioned by chemical techniques to give hexasaccharides, octasaccharides, decasaccharides, and mucopolysaccharide fragments of -14 residues and -16 residues that were able to complex with the protease inhibitor. Direct measurements of the kinetic behavior of the hexasaccharides, octasaccharides, and decasaccharides showed that these fractions greatly enhanced the rate of Factor Xa inactivation by antithrombin. Indeed, these species exhibited specific molar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 11 publications
5
112
0
Order By: Relevance
“…The necessary size for an oligosaccharide to inhibit thrombin activity is much longer (14-20 saccharides) than the pentasaccharide that is required to bind AT and inhibit factor Xa (23). A synthetic hexadecasaccharide (SR123781) that displays excellent anticoagulant activity against thrombin in vitro and in vivo has been produced (20).…”
Section: Structure and Anticoagulant Activity Relationshipmentioning
confidence: 99%
“…The necessary size for an oligosaccharide to inhibit thrombin activity is much longer (14-20 saccharides) than the pentasaccharide that is required to bind AT and inhibit factor Xa (23). A synthetic hexadecasaccharide (SR123781) that displays excellent anticoagulant activity against thrombin in vitro and in vivo has been produced (20).…”
Section: Structure and Anticoagulant Activity Relationshipmentioning
confidence: 99%
“…Tetrasaccharide c lacks the terminal sugar at the nonreducing end of pentasaccharide a. Tetrasaccharide d lacks the terminal residue from the reducing end of pentasaccharide a. A mixture of tetrasaccharides obtained by gel filtration (Oosta et al, 1981) was also tested. Virtually identical results were obtained when these heparin species were assayed on rat aortic and calf aortic SMC.…”
Section: Evidence For a Critical O-sulfate In The Pentasaccharidementioning
confidence: 99%
“…These experiments also indicated that both the N-and O-sulfates of heparin were necessary for antiproliferative activity, although the N-sulfates could be replaced with acetyl groups without significant loss of activity. Both the hexasaccharide fragment and the Ndesulfated, re-N-acetylated heparin are devoid of anticoagulant activity (Kazatchkine et al, 1981;Oosta et al, 1981), thus providing a chemical basis for the difference between the antiproliferative and anticoagulant activities of this glycosaminoglycan.In this paper, we have further analyzed the structural determinants of the antiproliferative effect of heparin. These experiments were done using synthetically prepared and therefore chemically defined heparin oligosaccharides.…”
mentioning
confidence: 99%
“…For example, a pentasaccharide sequence HexA-GlcN(NS)-HexA-GlcN(NS)-IdoA (2S) (Figure 2a) has been identified to be specific for fibroblast growth factor 2 (FGF2) binding, 32 another pentasaccharide sequence of heparin GlcN(6S)-GlcA-GlcN(NS,3S)-IdoA(2S)-GlcN(NS) (Figure 2b) is responsible for antithrombin III (AT-III, a serine protease inhibitor that blocks thrombin and factor Xa in the coagulation cascade) binding, 33 although a longer sequence (14-20 saccharide units) is required to accelerate the AT-III/thrombin interaction and inhibit thrombin activity. 34 Based on the structure of the AT-binding pentasaccharide, a new synthetic pentasaccharide anticoagulant under the trade name of Arixtra was approved by the FDA (Figure 2c). 33b A synthetic hexadecasaccharide (SR123781) that displays excellent anticoagulant activity against thrombin in vitro and in vivo was produced (Figure 3).…”
Section: Glycosaminoglycansmentioning
confidence: 99%